A co-dispersion nanosystem of graphene oxide @silicon-doped hydroxyapatite to improve scaffold properties. (1st February 2021) - Wang, Guoyong; Qian, Guowen; Zan, Jun; Qi, Fangwei; Zhao, Zhengyu; Yang, Wengjing; Peng, Shuping; Shuai, Cijun
Abstract: Poly l-lactic acid (PLLA) was limited in the further orthopaedic application due to its insufficient mechanical property and poor bioactivity. Graphene oxide (GO) is an effective reinforcement, whereas silicon-doped hydroxyapatite (Si-HA) possesses excellent bioactivity, but either GO or Si-HA tends to aggregate in PLLA matrix. In this study, a GO@Si-HA nanosystem was achieved by in-situ growth of Si-HA on GO, and then incorporated into PLLA scaffold fabricated by laser sintering technology. On one hand, Si-HA on the surface of GO effectively prevented the aggregation of GO by acting as a barrier between GO nanosheets. On the other hand, GO hindered the aggregation of Si-HA by means of anchoring Si-HA. Results displayed that the compressive strength and modulus of the PLLA/GO@Si-HA composite scaffold were enhanced by 85% and 120%, respectively. Meanwhile, the scaffold exhibited significantly improved bioactivity, and consequently promoted cell adhesion, proliferation and differentiation. The developed PLLA/GO@Si-HA composite scaffold with excellent mechanical properties and superior bioactivity could serve as a promising substitute for bone repairing. Graphical abstract: Unlabelled Image Highlights: A co-dispersion nanosystem of GO@Si-HA was constructed via in-situ growth technique. The dispersibility of GO and Si-HA nanoparticles in PLLA scaffold can be simultaneously improved, achieving a co-dispersion reinforcing effect. The PLLA/GO@Si-HA scafffold was prepared via selective laser sintering. Compressive strength and modulus of the scaffold have increased by 85% and 120% compared with PLLA scaffolds. The scaffold promoted cell adhesion, proliferation and differentiation.